Profit efficiency among Kenyan smallholders milk producers: A case study of Meru-South district, Kenya - Karanja Ng'ang'a, Stanley; Kungu, J.; Ridder, N.A. de; Herrero, Mario (2010)
Production inefficiency is usually analyzed by economical efficiency, which is composed of two components-technical and allocative efficiencies. This study provided a direct measure of production efficiency of the smallholder milk producers in Kenya using a stochastic profit frontier and inefficiency model. The primary data were collected, using IMPACT (intergrated modeling platform for mixed animal crops systems) structured questionnaire and includes four conventional inputs and socio-economic factors affecting production. The result showed that profit efficiencies of the sampled farmers varied widely between 26% and 73% with a mean of 60% suggesting that an estimated 40% of the profit is lost due to a combination of both technical and allocative inefficiencies in the smallholder dairy milk production. This study further observed that level of education, experience, and the size of the farm influenced profit efficiency positively while profit efficiency decreased with age. This implies that profit inefficiency among smallholder dairy milk producers can be reduced significantly with improvement in the level of education of sampled farmers.